A treasure to be plucked - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Though undervalued in the past, leafy vegetables are a key ingredient in the diets of ACP countries. Recently, researchers have shown strong interest in these traditional greens for their high nutritional value and economic potential.